Triggered release of proteins from emulsan–alginate beads - Castro, Guillermo Raúl (2005)
Emulsan/alginate beads were studied for protein adsorption and stability in the context of controlled release. The beads, 400F80 Am diameter with approximately 10% emulsan content, offer unusual opportunities for delivery of proteins due to the natural ability of emulsan to bind proteins, coupled with the selective biological activation features of this complex lipoheteropolysaccharide. The binding capacity of azo-bovine serum albumin by the emulsan/alginate beads was 0.637 ± 0.004 vs. 0.170 ± 0.007 μg/mg for beads formed from alginate alone. In additional protein adsorption experiments, the lipase and subtilisin maintained activity when adsorbed to the emulsan/alginate beads albeit with lower specific activity when compared to the enzyme free in solution. However, the half life of the adsorbed enzyme was significantly higher than the free forms. To explore functional utility of this system, two types of triggered release were studied in the context of these bead systems. First, azo-BSA as a model protein was physically bound to emulsan/alginate beads and then selectively released by triggering with subtilisin, a serine protease, which cleaves the azo dye, sulfanilic acid, from the bound protein. In absence of subtilisin no triggered release was observed. Second, azo-BSA as a prodrug model, was adsorbed to the emulsan/alginate beads and then release of the dye was demonstrated by lipase treatment which cleaves the fatty acid esters from the emulsan structure to release the bound protein. The results establish the versatility and utility of emulsan-based beads for protein binding and triggered release.